Environmental design guidelines for digital fabrication - Agustí-Juan, Isolda; Habert, Guillaume (Journal of cleaner production, 2017)
Digital fabrication represents an innovative technology with the potential of expanding the boundaries of architecture. The potential to fabricate elements directly from design information is transforming many design and production disciplines. In particular, 3D printing has become the key of modern product development. As the use of additive manufacturing grows, research into large-scale processes is beginning to reveal potential applications in construction. The combined methods of computational design and robotic fabrication have the well-demonstrated potential to create formal and structural advances in architecture. However, their potential contribution to the improvement of sustainability in construction must be evaluated. In this study, we identified environmental guidelines to be considered during the design of digitally fabricated architecture. The key parameters were extracted from the Life Cycle Assessment (LCA) of three case studies. The environmental assessment performed indicated that the relative sustainability of the projects depended primarily on the building material production. Specifically, the impact of digital fabrication processes was negligible compared to the materials manufacturing process. Furthermore, the study highlighted the opportunities of integrating additional functions in structural elements with digital fabrication to reduce the overall environmental impact of these multi-functional elements. Finally, the analysis proved the potential of digital fabrication to reduce the amount of highly industrialized materials in a project, which are associated with high environmental impacts. •Digital fabrication analysed from an environmental point of view.•LCA comparison of digital fabrication and conventional construction processes.•Identification of key elements to consider during digital fabrication design.